Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

La rue Saint-Denis (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-21-00
Keywords: Cherrier; Côme-Séraphin; Hôpital Sainte-Justine; Levasseur; Irma; Massicotte; Édouard-Zotique; Patrimoine; Plateau Mont-Royal (arrondissement); Saint-Denis (rue)

Historiennes engagées et femmes patriotes: la révolution de 1837-1838 et la place des femmes dans l'histoire du Québec - Arsenault, Mathieu (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Histoire; Rébellions

L’invention du Vieux‑Montréal. Les représentations d’un quartier historique dans les guides touristiques (19e‑20e siècles) - Drouin, Martin (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-23-00/2023-24-00
Keywords: Patrimoine; Quartiers; Tourisme; Vieux-Montréal

Hochelaga Depicta (1839) ou Montréal à l'infini présent - Lacroix, Laurier (Les cahiers des Dix, 2023)
Keywords: Histoire

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
issued: 2022-21-00/2022-23-00
Keywords: Archives; Femmes; Écrivains

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Translators: _:n461 Translators: _:n62043
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n199 Translators: _:n62269
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n188 Translators: _:n62336
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan M. (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Astronomie; Géologie; Notman; William; Photographie

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Pour la mémoire collective. Rien n'est jamais perdu - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

Deux pichets commémoratifs d'un moment marquant. 1846. L'abolition des Corn Laws - Pothier, Louise (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

La protection et la transmission du patrimoine montréalais dans la deuxième moitié du XIXe siècle : l'exemple de la Numismatic and Antiquarian Society of Montreal - Vaudry-Levasseur, Flavie (Université du Québec à Montréal, 2021)
Keywords: Archéologie; Numismatie; Patrimoine

DUMONT, GEORGES-ALMA (Dictionnaire biographique du Canada, 2020)

Le Club des archères de Montréal existait-il réellement? - Martin, Gabriel (Histoire Québec, 2020)
Number: 1-2
Keywords: Clubs; Femmes; Histoire; Montreal Ladies Archery Club / Montreal Archery Club

Réflexions autour de deux pichets commémoratifs découverts sur le site du parlement à Montréal et l’abolition des Corn Laws en 1846 - Pothier, Louise (Les Cahiers des Dix, 2020)
Number: 74
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Histoire scientifique du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-23-00
Keywords: Géologie; Institut des sourdes-muettes; Institut des sourds-muets; Médecine; Sourds

Le recours aux technologies numériques pour l'étude de contenus à caractère historique et archéologique: l'exemple du site de l'ancien marché Sainte-Anne et du Parlement de la province du Canada - Charbonneau, Nathalie; Thirion, Anna (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Archéologie; Histoire; Marchés; Parlement; Patrimoine; Sainte-Anne (marché)

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

L'odyssée des archives de la Société Historique de Montréal - Robert, Mario (Montréal en tête, 2019)
issued: 2019-22-00
Keywords: Archives; Société historique de Montréal

Denis Benjamin-Viger en 1809 et en 1831: de la répétition de l'histoire au crescendo de l'inacceptable - Raymond-Dufour, Maxime (Revue d'histoire de l'Amérique française, 2018)
issued: 2018-24-00/2018-21-00
Keywords: Histoire; Viger; Denis-Benjamin

Managing and Analyzing Archaeological Data with GIS: the Case of Place D’Youville, Montréal - Robichaud, Léon; Van Gijseghem, Hendrik; Petit, Kim; Burgess, Joanne (Proceedings of the 3rd Digital Heritage International Congress and 2018 24th International Conference on Virtual System & Multimedia, 2018)
Reporter: Proceedings of the 3rd Digital Heritage International Congress and 2018 24th International Conference on Virtual System & Multimedia
Keywords: Archéologie; Histoire; Places publiques; Youville (place d')

Le temps d'une leçon: l'utilisation et le rôle des musées scolaires dans les écoles de filles entre 1860 et 1970 au Québec - Thiboutot, France (Le patrimoine des communautés religieuses. Empreintes et approches, 2018)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Musées; Patrimoine; Villa-Maria

Louis-Wilfrid Marchand (1833-1896), avocat, trésorier de la SHM et chercheur en histoire - Tremblay, Serge (Montréal en tête, 2018)
issued: 2018-23-00
Keywords: Avocats; Histoire; Journalistes; Minerve (La); Patrie (La); Société historique de Montréal

A Sense of Place: Montreal before Cartier - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Archéologie; Autochtones; Dawson; William; Français; Hochelaga; Iroquoiens; Iroquois; Place Royale; Vieux-Montréal

À la recherche d’Hochelaga - Gates St-Pierre, Christian (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Cartier; Jacques; Hochelaga

La trahison d'un amoureux des "vieilles lois françaises"? Louis-Joseph Papineau et le paradoxe du seigneur républicain - Guimond, Olivier (Université de Sherbrooke, 2017)
Keywords: Papineau; Louis-Joseph; Rébellions; Seigneurie

Le Parlement du Canada-Uni à Montréal, 1843-1849: Un site archéologique exceptionnel - Pothier, Louise; Van Gijseghem, Hendrik (Revue parlementaire canadienne, 2017)
issued: 2017-24-00
Keywords: Archéologie; Marchés; Parlement; Sainte-Anne (marché)

The General: A History of the Montreal General Hospital - Hanaway, Joseph; Burgess, John H. (McGill-Queen's University Press, 2016)
Keywords: Hôpitaux; Montreal General Hospital

Papineau, ''celui qui n'écrit pas'': l'inscription de l'homme politique dans l'histoire littéraire québécoise - Livernois, Jonathan (Voix et Images, 2016)
issued: 2016-23-00
Keywords: Histoire; Papineau; Louis-Joseph; Écrivains

Collectionner à Montréal au 19e siècle: Gerald E. Hart et la construction d'une pratique utile - Truchon, Caroline (À la recherche du savoir: Nouveaux échanges sur les collections du Musée McCord / Collecting Knowledge: New Dialogues on McCord Museum, 2016)
Keywords: Numismatie

An Extensive and Unknown Portion of the Empire: The Montreal Natural History Society's Survey of Rupert's Land, 1827-1830 - Little, Geoffrey (Université Concordia, 2015)
Keywords: Histoire naturelle; Société d'histoire naturelle

Why Did We Choose to Industrialize? Montreal, 1819-1849 - Sweeny, Robert (McGill-Queen's University Press, 2015)

L'Institut canadien de Montréal et l'intelligentsia protestante: réactions, relations et perceptions - Cousson, Claire (Huguenots et protestants francophones au Québec, 2014)
Keywords: Francophones; Institut canadien; Protestants

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

Entre champ d'intérêt et objet de pression, le patrimoine. Les luttes pour la conservation du Château Ramezay, 1893-1932 - Hébert, Karine (De la représentation à la manifestation. Groupes de pression et enjeux politiques au Québec, XIXe et XXe siècles, 2014)
Keywords: Conservation; Patrimoine; Ramezay (château de)

Icônes de collections - Truchon, Caroline (Continuité, 2014)
issued: 2014-24-00
Keywords: Histoire naturelle; Numismatie

Le règne de la scientificité: histoire de l'étiologie des maladies infectieuses dans la presse médicale du Québec, 1840-1880 - Beaudry, Louka (Université de Montréal, 2013)
Keywords: Médecine

The Sulpician Identity - Deslandres, Dominique (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46717
Keywords: Communautés religieuses; Sulpiciens

Les débuts de la Société d’archéologie et de numismatique de Montréal - Tremblay, Alex (Cap-aux-Diamants, 2013)
issued: 2013-24-00
Keywords: Archéologie; Numismatie

Fabriquer l'erreur après 1950 - Lamonde, Yvan; Livernois, Jonathan (Papineau, erreur sur la personne, 2012)
Keywords: Papineau; Louis-Joseph

Fabriquer l'erreur avant 1950 - Lamonde, Yvan; Livernois, Jonathan (Papineau, erreur sur la personne, 2012)
Keywords: Papineau; Louis-Joseph

Papineau: erreur sur la personne - Lamonde, Yvan; Livernois, Jonathan (Boréal, 2012)
Keywords: Papineau; Louis-Joseph

L'esprit des lieux: Montréal avant Cartier - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Archéologie; Autochtones; Dawson; William; Français; Hochelaga; Iroquoiens; Iroquois; Place Royale; Vieux-Montréal

Pierre Vallières ou le danger d'occulter le passé - Antaya, Felipe (Université du Québec à Trois-Rivières, 2011)
Keywords: Franciscains; Idéologies

Pratiques et réseaux des naturalistes au Québec, 1850-1920 - Desmeules, Mélanie (Université Laval, 2011)
Keywords: Botanique; Faune; Flore; Histoire naturelle; Marie-Victorin; Frère; Natural History Society; Société d'histoire naturelle

L'évolution des sciences au Canada français examinée à partir de la mycologie - Gaudreau, Guy (Mens, 2011)
issued: 2011-21-00
Keywords: Botanique; Flore; Marie-Victorin; Frère

Science Culture in English-Speaking Montreal, 1815-1842 - Kuntz, Harry (Université Concordia, 2010)
Keywords: Anglophones; Natural History Society

Le musée de l’Institut canadien de Montréal (1852-1882), un projet inachevé - Lacroix, Laurier (Les Cahiers des dix, 2010)
Number: 64
Keywords: Institut canadien; Musées

Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (VLB Éditeur, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger; Jacques

Récits du XIXe siècle: structure et contenu du discours historiographique au Canada au XIXe siècle: Garneau, Kingsford, Rameau de Saint-Père, Smith - Couture, Claude; Defert, Jean-Jacques (Presses de l'Université Laval, 2009)
Keywords: Histoire; Historiens

L'iconographie rébellienne, la face cachée de l'historiographie des rébellions de 1837-1838: quelques études de cas - St-Jean, France (Mens, 2009)
issued: 2009-23-00
Keywords: Histoire; Rébellions

1858-2008. Numéro souvenir du 150e anniversaire de la Société historique de Montréal (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Histoire; Historiens; Société historique de Montréal

Les fondateurs de la Société historique de Montréal - Beaudoin, Léo; Bellemare, Georges (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Baby; Louis-François Georges; Baudry; Joseph-Ubalde; Bellemare; Raphaël; Histoire; Historiens; Huguet-Latour; Louis-Adolphe; Société historique de Montréal; Viger; Jacques

Les lignes de faîte de l'historiographie des rébellions de 1837-1838 - Collin, Marc (Bulletin d'histoire politique, 2008)
issued: 2008-23-00
Keywords: Histoire; Rébellions

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

"Rien n'est beau que le vrai". L'histoire aux débuts de la Société historique de Montréal - Roy, Fernande (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Histoire; Historiens; Société historique de Montréal

Louis-François-George Baby (1832-1906). Bourgeois montréalais, cofondateur et 3e président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2007)
issued: 2007-21-00/2007-22-00
Keywords: Baby; Louis-François Georges; Bourgeoisie; Histoire; Numismatie; Société historique de Montréal

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières; Pierre

Représentations identitaires - Deslandres, Dominique (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

La route et ses passagers dans les romans rédigés au Québec au XIXe siècle: outils de représentation de la mobilité - Bousquet, Eveline (Université de Montréal, 2006)
Keywords: Roman

The Curious Tale of the Scots and the Fur Trade: An Historiographical Account - Bumsted, J. M. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Fourrure; Écossais

Autour de Chénier: les Rebellions et la conscience historique canadienne et québécoise - Collin, Marc (Université Laval, 2006)
Keywords: Histoire; Rébellions

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Sir William Logan and Sir J.W. Dawson: Victorian Geology as Scottish Science in a New World Environment - Zeller, Suzanne (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Dawson; William; Géologie; Logan; William Edmond; Écossais

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

McEACHRAN, DUNCAN McNAB - Goulet, Denis; Jean, Frédéric (Dictionnaire biographique du Canada, 2005)

JETTÉ, JULES - Laugrand, Frédéric (Dictionnaire biographique du Canada, 2005)

Les bouteilles de verre du château de Vaudreuil: une archéologie de l'alcool à Montréal, au XVIIIe siècle - Losier, Catherine (Université de Montréal, 2005)
Keywords: Alcool; Archéologie

McCORD, DAVID ROSS - Miller, Pamela (Dictionnaire biographique du Canada, 2005)

RUTTAN, ROBERT FULFORD - Nicholls, Robert V. V. (Dictionnaire biographique du Canada, 2005)

DUCLOS DE CELLES, ALFRED - Roy, Fernande (Dictionnaire biographique du Canada, 2005)

CAMPBELL, ROBERT - Shute, Dan (Dictionnaire biographique du Canada, 2005)

Seigneur, Faites Que Je Voie: One-man's Quiet(ish) Revolution - Henderson, Robert K. (The Beaver, 2004)
issued: 2004-02/2004-03

Carving the Past in Stone: le Monument aux Patriotes - O'Flaherty, Rosemary (Université Concordia, 2004)
Keywords: Monuments; Rébellions

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Ville de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal (suite*) - Beaudoin, Léo (Montréal en tête, 2003)
issued: 2003-24-00
Keywords: Chauveau; Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

La contribution entomologique et taxinomique de l'abbé Léon Provancher - Desmeules, Mélanie (Université du Québec à Chicoutimi, 2003)
Keywords: Entomologie; Flore

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: McEachran; Duncan McNab; Université McGill; École de médecine vétérinaire

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
issued: 2002-08/2002-11
Keywords: Criminalité; Médecine; Université McGill; Étudiants

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2002)
issued: 2002-23-00
Keywords: Chauveau; Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

Toronto vs Montreal: The Struggle for Financial Hegemony, 1860-1875 - Masters, D.C. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Banques; Métropole

Les Canadiens français, l'histoire et la démocratie: l'interprétation de Pierre Elliott Trudeau - Ouellette, Mélanie (Mens, 2000)
issued: 2000-23-00
Keywords: Trudeau; Pierre Elliott

La recherche sur l'histoire de la presse québécoise. Bilan et perspectives - Roy, Fernande (Recherches sociographiques, 2000)
Number: 1
Keywords: Histoire